The Effect of Project Based Learning on Students’ Learning Outcomes in Colloidal System - Elvi Safitri; Esnawi; Abraham Rahman (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This study aims to analyze the effect of the Project Based Learning (PjBL) model on students’ chemistry learning outcomes on the colloid system topic in Grade XI of SMA Negeri 1 Raha. This research employed a quasi-experimental design with a pretest–posttest control group design. The sample consisted of 60 students divided into an experimental class and a control class. The research instruments included a validated multiple-choice achievement test and observation sheets of students’ learning activities and instructional implementation. Data were analyzed using N-gain analysis, normality test, homogeneity test, and an independent sample t-test. The results showed that the posttest and N-gain scores of the experimental class were higher than those of the control class. The t-test result indicated a significant difference between the two classes (p < 0.05). Students’ learning activities in the experimental class were categorized as very good. Thus, PjBL was proven to be more effective than direct instruction.